2019
DOI: 10.1186/s12882-019-1629-y
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular events in hemodialysis patients; a retrospective observational study

Abstract: BackgroundThis study reports findings in subjects who underwent brain imaging for any reason, and examined factors influencing cerebrovascular events (CVEs) in hemodialysis (HD) patients.MethodsWe reviewed the files of patients on HD between January 2015 and January 2018. A total of 432 patients who underwent HD for at least 5 months by the January 2015 and who were older than 18 years were included in the study; 264 had been examined by cerebral computed tomography or magnetic resonance imaging examination wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…One prospective cohort study evaluated the risk of hemorrhagic transformation in ischemic stroke [23]. A retrospective study showed hemorrhagic or ischemic stroke seen more in the elderly population [24]. Whereas a prospective study showed an increased risk of HT with the progression of renal dysfunction [23,25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One prospective cohort study evaluated the risk of hemorrhagic transformation in ischemic stroke [23]. A retrospective study showed hemorrhagic or ischemic stroke seen more in the elderly population [24]. Whereas a prospective study showed an increased risk of HT with the progression of renal dysfunction [23,25].…”
Section: Resultsmentioning
confidence: 99%
“…Whereas a prospective study showed an increased risk of HT with the progression of renal dysfunction [23,25]. Table 1 presents the risk of stroke in dialysis patients in relevant studies [17][18][19][20][21][22][23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the general population, patients undergoing maintenance hemodialysis are at a higher risk of cerebral hemorrhage [ 15 ], which is associated with the high prevalence of hypertension, vascular comorbidities linked to kidney impairment, and complications resulting from uremia, such as vascular calcification and malnutrition-inflammation-atherosclerosis syndrome [ 16 ]. The use of heparin is essential for dialysis therapy, but is hazardous in the case of cerebral hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Taiwan shows that circulatory P levels > 3.925 mg/dL were associated with severe WMHs in a community-based longitudinal aging Study (Chung et al, 2019). A study in Turkey follows subjects who underwent brain imaging for any reason, reported that CSVD patients had lower P than normal subjects (Ozelsancak, Micozkadioglu, Torun, & Tekkarismaz, 2019). In US veterans population, high serum P is associated with CSVD and dementia, and this relationship is more signi cantly in participants <60 years old (Li, Xie, Bowe, Xian, & Al-Aly, 2017).…”
Section: Discussionmentioning
confidence: 99%